Case Report: COVID-19 Pneumonia Following Left Pneumonectomy for Lung Cancer Complicated by Empyema and Bronchopleural Fistula - Testori, Alberto; Giudici, Veronica M.; Alloisio, Marco; Cioffi, Ugo (Frontiers in Surgery, 2021)
Background: Venous and arterial thromboembolism is commonly reported in critically ill Covid 19 patients, although there are still no definitive statistical data regarding its incidence. Case presentation: we report a case of a patient who fell ill with Covid during hospitalization for a pneumonectomy complicated by empyema and bronchopleural fistula. The patient, despite being cured of COVID, died after 14 days for pulmonary thromboembolism. Conclusion: Our case strengthens the suggestion of adequate thromboprophylaxis in all hospitalized COVID patients and of increasing prophylaxis in critically ill patients even in the absence of randomized studies